PERIODS OF THE EMERGENCE AND DEVELOPMENT OF ISLAM IN THE UNITED STATES - Otabek Anvarovich Mavlonov (Scholar Express Journal, 2023)
The USA is a country with great cultural phenomena, one of which is considered to be Islamic society. Nevertheless, Islamic community is steadily increasing in America and the number of mosques and Muslim schools, which are becoming most popular among the US population, is increasing fast. This article deals with the beginning of Islamic history, development stages and formation of Muslim community in America. Additionally, the article contains information on the life of American Muslims before and after September 11, 2001, the event that changed the attitude of other nations not only to American Muslims, but also the entire Islamic World as well.
Keywords: Muslims; America; slavery